The Role of international trade in the post-2015 development agenda (UN New YorkUS, 2014)
Looks at the identifying the types of national policies and international contexts that would harness the enabling power of trade for development, and against that background, design a coherent framework in which targets and indicators are sustained with respect to the policy matrix and conditions required to bring about the desired goals.
Keywords: INTERNATIONAL TRADE